PEACE EDUCATION FOR NATIONAL SECURITY AND INTERCULTURAL INTEGRATION IN A MULTICULTURAL SOCIETY: THE COUNSELLING PERSPECTIVE - IDOWU, Amaihian, P. (Journal of Professional Counselling, 2025)
The inculcation and integration of culture of peace and security among the diverse group in a multicultural society lay credence to peaceful co-existence divulge of violence, insecurity, conflicts and inability to tolerate and acculturate, non-acceptance of other people’s cultural heritage. A country without any of socio-cultural, religion and values difference abhor peace and co-exist through acquisition of Peace education, and multicultural Education that give values to Unity and Peace. The paper is aimed at examining the roles of Counselling towards culture of peace, security and integration in a multicultural society. Identify the causes of insecurity violence and disunity such as non-inclusion of Peace Education in the school curriculum to train students about peaceful co-existence, poverty, food shortage, cultural and ethnic discrimination, non-acceptance of other people’s opinion and cultural values, the ethnoreligious indoctrination which result to restiveness, frustration, death, displacement insecurity and genocide being experience in all part of the country. To maintain peace and integration of the diverse people, will require effective strategies and campaign for peace, reconciliation of the differences which could be achieved with the introduction of counselling services, promoting unity, stability and peaceful co-existence. Recommendation was made that, there should be adequate counselling programmes, peace awareness and inculcation of peace Education in the school curriculum and promoting cultural integration through inter-ethnic marriages, cultural festival, exchange programmes among various group